Alliance portfolio management capabilities, corporate entrepreneurship, and relative firm performance in SMEs. (4th March 2023) - Sakhdari, Kamal; Burgers, J. Henri; Davidsson, Per
ABSTRACT: This article shows how small- and medium-sized enterprises (SMEs) can enhance the level of corporate entrepreneurship through alliance management capabilities. The findings from a sample of 272 suppliers to the mining industry demonstrate that the constituting dimensions of alliance portfolio management capability (that is, partnering proactiveness, relational governance, and portfolio coordination) positively affect corporate entrepreneurship. Moreover, corporate entrepreneurship mediates the effects of these dimensions on firm performance. These findings improve our understanding of how organizational capabilities enable SMEs to mitigate their lack-of-resources problem while engaging in interfirm relationships to better utilize corporate entrepreneurship for increasing firm performance.